Posthumanism as Ideology and Research Perspective - Bogusławski, Marcin M. (Hybris, 2019)
My article aims at showing that posthumanism is an ideology that finds its extension in research perspective called posthumanities. The notion of ideology I apply is not a negative one. Ideology is an intrinsic element of social life, and its illusive character essentially means that it serves as a tool for man to orientate in the world. It also gives an account of the current challenges faced by society and of the contradictions related to them. In my opinion, the contradiction embedded in posthumanism is that it excludes in a principled way all kinds of humanism/anthropocentrism, but is virtually unable to escape some form of humanism and anthropocentrism. They are necessary to do justice to the worlds of other animal species, to substantiate the ethical order that posthumanists feel close to, or to be able to use the notion of agency.